The Covid-19 crisis and consumption: Survey evidence from six EU countries - Dimitris Christelis; Dimitris Georgarakos; Tullio Jappelli; Geoff Kenny (European Central Bank (ECB), 2020)
Using new panel data from a representative survey of households in the six largest euro area economies, the paper estimates the impact of the Covid-19 crisis on consumption. The panel provides, each month, household-specific indicators of the concern about finances due to Covid-19 from the first peak of the pandemic until October 2020. The results show that this concern causes a significant reduction in nondurable consumption. The paper also explores the potential impact on consumption of government interventions and of another wave of Covid-19, using household-level consumption adjustments to scenarios that involve positive and negative income shocks. Fears of the financial consequences of the pandemic induce a significant reduction in the marginal propensity to consume, an effect consistent with models of precautionary saving and liquidity constraints. The results are robust to endogeneity concerns through use of panel fixed effects and partial identification methods, which account also for time-varying unobservable variables, and provide informative identification regions of the average treatment effect of the concern for Covid-19 under weak assumptions.
Keywords: D12; D81; E21; G51; H31; 330; Covid-19; Consumption; Marginal Propensity to Consume; Financial concerns; Fiscalpolicies